2005
DOI: 10.1186/1465-9921-6-94
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HLA-DRPheβ47 as the susceptibility marker of hypersensitivity to beryllium in individuals lacking the berylliosis-associated supratypic marker HLA-DPGluβ69

Abstract: We conclude that HLA-DPGlu69 is the primary marker of Be-hypersensitivity and HLA-DRPhe47 is associated with BH in Glu69-negative subjects, likely playing a role in Be-presentation and sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 36 publications
3
34
1
Order By: Relevance
“…Difference in HLA-DRB1 associations with CBD and beryllium sensitization might account for the varying results because some DRB1 alleles are in linkage disequilibrium with the TNF gene and a high percentage of the US patients with CBD in both the Dotti et al 11 and Gaede et al 12 studies were associated with HLA-DR genotypes not found in other studies to date. 6,9,32,33 TNF promoter polymorphisms have been associated with severity of disease, including the granulomatous lung diseases hypersensitivity pneumonitis 34 and sarcoidosis. 17,35 The 2307A allele has been observed at increased frequency in patients with sarcoidosis with Lofgren syndrome, a less severe form of the disease with spontaneous resolution, 17,29 whereas other studies have found associations between the 2307A allele and more severe phenotypes, such as cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Difference in HLA-DRB1 associations with CBD and beryllium sensitization might account for the varying results because some DRB1 alleles are in linkage disequilibrium with the TNF gene and a high percentage of the US patients with CBD in both the Dotti et al 11 and Gaede et al 12 studies were associated with HLA-DR genotypes not found in other studies to date. 6,9,32,33 TNF promoter polymorphisms have been associated with severity of disease, including the granulomatous lung diseases hypersensitivity pneumonitis 34 and sarcoidosis. 17,35 The 2307A allele has been observed at increased frequency in patients with sarcoidosis with Lofgren syndrome, a less severe form of the disease with spontaneous resolution, 17,29 whereas other studies have found associations between the 2307A allele and more severe phenotypes, such as cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…Amicosante el al. [23] found HLA-DPB1-Glu69 markers to have highest frequency in berylliosis patients (86%) compared with sensitized individuals (55%) and nonsensitized beryllium-exposed controls (48%). But in addition, they also found HLA-DRPheb47 to be independently associated with BeH in a group of 22 subjects who were negative for the HLA-DPB1-Glu69 allele.…”
Section: Genetic Susceptibilitymentioning
confidence: 90%
“…Thus, the presence of Glu69-positive HLA-DPB alleles can only serve as a marker for the risk of sensitisation and not as a diagnostic criterion [2]. Extended genetic testing for supratypic markers, as suggested for HLA-DRPheb47, might give additional information on the risk of beryllium sensitisation [31]; however, a high frequency of this named marker in sarcoidosis [21,32] makes it unlikely that this approach will improve diagnosis of CBD in the near future.…”
Section: Discussionmentioning
confidence: 99%